2005
DOI: 10.1103/physrevc.72.054306
|View full text |Cite
|
Sign up to set email alerts
|

High-Kstates in the odd-odd nuclideRe180

Abstract: The structure of the deformed, doubly odd nuclide 180 Re has been studied by γ -ray and conversion-electron spectroscopy using the 174 Yb( 11 B,5n) reaction with a pulsed 71 MeV beam of 11 B ions. Several of the previously known intrinsic states have been given revised spin and parity assignments. Rotational bands are observed with K π = (4 + ), (5 − ), (7 + ), 8 + , 9 − , 13 + , 14 − , 15 − , 16 + , 21 − , and (22 + ). Among these, a four-quasiparticle t band is identified, which is already energetically favo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 47 publications
0
2
0
Order By: Relevance
“…Band 3 is, hence, interpreted as a four-quasiparticle band. Considering the active quasiparticle orbitals, two candidates for a four-quasiparticle band with K π = 14 − are π 9/2 − [ [46,49], with K eff = 16.96 and a bandhead energy E = 1755 keV. That band was described as π 9/2 − [514] ⊗ ν5/2 − [512], 7/2 − [514], 9/2 + [624], K π =15 − .…”
Section: Bandmentioning
confidence: 99%
“…Band 3 is, hence, interpreted as a four-quasiparticle band. Considering the active quasiparticle orbitals, two candidates for a four-quasiparticle band with K π = 14 − are π 9/2 − [ [46,49], with K eff = 16.96 and a bandhead energy E = 1755 keV. That band was described as π 9/2 − [514] ⊗ ν5/2 − [512], 7/2 − [514], 9/2 + [624], K π =15 − .…”
Section: Bandmentioning
confidence: 99%
“…The present work is concerned with an odd-odd, neutrondeficient isotope of rhenium, 174 75 Re 99 . Until recently, the lightest odd-odd rhenium isotope observed with a multiquasiparticle isomer was 180 Re [1,3], but Guo et al [4] have reported evidence for the existence of a strongly populated, four-quasiparticle isomer in 174 Re, with a half-life exceeding 1 μs. In this work, a new study of 174 Re is presented.…”
Section: Introductionmentioning
confidence: 99%